2017
DOI: 10.1007/s11205-017-1725-y
|View full text |Cite
|
Sign up to set email alerts
|

“It’s for Our Education”: Perception of Parental Migration and Resilience Among Left-behind Children in Rural China

Abstract: As a result of China's rural-urban bifurcation, millions of rural Chinese children grow up in the absence of one or both parents due to work migration. Contrary to the dismal picture of left-behind children that is depicted by the mass media, comparative studies based on large-scale survey data suggest that left-behind children do not fare worse than those who live with both parents. Researchers have suggested that the positive effects of remittance might outweigh the negative effects of parental absence, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 52 publications
5
33
0
Order By: Relevance
“…Another potential reason is that children who grow up without their parents may learn to adapt to such adverse circumstances, thereby creating more opportunities for them to exercise agency and independence, increasing their resilience and ultimately reducing the negative impact on their mental health. This hypothesis is supported by studies conducted both in rural China and in other contexts [ 68 , 69 ]. It also aligns with the challenge model of resilience theory, which posits that exposure to certain levels of adversity increases one’s ability to cope with future setbacks [ 70 ].…”
Section: Discussionsupporting
confidence: 58%
“…Another potential reason is that children who grow up without their parents may learn to adapt to such adverse circumstances, thereby creating more opportunities for them to exercise agency and independence, increasing their resilience and ultimately reducing the negative impact on their mental health. This hypothesis is supported by studies conducted both in rural China and in other contexts [ 68 , 69 ]. It also aligns with the challenge model of resilience theory, which posits that exposure to certain levels of adversity increases one’s ability to cope with future setbacks [ 70 ].…”
Section: Discussionsupporting
confidence: 58%
“…In all, LBC can demonstrate extraordinary resilience. Hu (2019) found that the way that adolescent LBC interpret parental migration is a significant contributing factor to their resilience. In this study, LBC who had a positive perception of their parents' rationale for labor migration demonstrated higher resilience.…”
Section: Physical and Emotional Functioningmentioning
confidence: 96%
“…Also, parental migration does not negatively affect educational outcome via worsening adolescents’ psychological well-being, because left-behind adolescents do not differ significantly from their non-left-behind counterparts as measured by depressive symptoms in this study. This could be due to the role of extended family members in caring and supervising adolescents in the absence of parents, and the fact that middle school adolescents in rural China spend a lot of time on campus studying, socializing, living with peers, and being closely supervised by teachers (Hu, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Many migrant parents learn from their own experiences, or by observing the urban industrial world around them, that education is the key to white-collar jobs, and is perhaps the only way for their children to achieve a different life from theirs. Despite the physical distance, migrant parents try to maintain frequent communications with their children and monitor their health status and school performance (Hu, 2017). They tend to tell their own stories as counterexamples to emphasize the importance of educational qualification to their children.…”
Section: The Social Remittance Perspectivementioning
confidence: 99%